Extraction of Terpenoids from Pine Needle Biomass Using Dimethyl Ether - Gary S. Groenewold; Christopher Orme; Caleb Stetson; Rebecca M. Brown; Lynn M. Wendt; Aaron D. Wilson (Separations)
Pine needles are an industrial feedstock for extracts used in a variety of applications, but conventional extraction methods often result in a degradation of the terpenoid compounds that naturally occur in loblolly pine (Pinus taeda). Separation of these compounds from pine biomass is an energy-intensive operation, typically requiring a significant input of thermal energy. An alternative separation approach with potential energy savings is extraction with a condensable gas, namely, dimethyl ether. Biomass materials are exposed to liquid dimethyl ether under pressure, which mobilizes the organics. The extract is then separated from the insoluble pine matter, and dimethyl ether is volatilized away from the separated organic species. A variety of terpene derivatives were extracted from pine needle biomass using this approach, including monoterpenes, sesquiterpenes, and related oxygenates, which were identified using two-dimensional gas chromatography/mass spectrometry. Additionally, the dimethyl ether-treated needles resemble needles subjected to low-temperature drying, whereas needles treated with a high-temperature drying method appear to have shrunken structures. The results suggest that dimethyl ether extraction has significant potential for separating valuable organics from complex matrices without the application of thermal energy during treatment.